Socio- Komunikasi Partisipatif Pertanian Perkotaan dalam Pemberdayaan Masyarakat Melalui 1000 Lubang Hidroponik KWT Harmonis Rawacana, Kota Tangerang 2023 - Huda Alvian Mahesa; Ukon Furkon Sukanda; Ari Suseno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A participatory activity in the community has been carried out in the form of transfer of appropriate technology for cultivating plants, vegetables organically or hydroponically which aims to optimize the use of yard land or empty land by using the application through planting 1000 hydroponic holes. This study aims to identify what factors influence KWT Harmonis Rawacana starting from community participation to improve family economy through 1000 hydroponic holes. The results of the study showed that KWT Harmonis Rawacana that the community was involved in the communication planning process through (A) Adaptation, (G) Utilization of harvest results, (I) integrity, and (L) Maintenance of patterns for women farmer groups, but the government continues to strive to increase independence and welfare to improve family economy in the utilization of empty land. This empowerment can increase income by meeting physical, spiritual, and social needs by utilizing community participation and resources available in 1000 Hydroponic holes of KWT Harmonis Rawacana, Tangerang City 2023. A participatory activity in the community has been carried out in the form of transfer of appropriate technology for cultivating plants, vegetables organically or hydroponically which aims to optimize the use of yard land or empty land by using the application through planting 1000 hydroponic holes. This study aims to identify what factors influence KWT Harmonis Rawacana starting from community participation to improve family economy through 1000 hydroponic holes. The results of the study showed that KWT Harmonis Rawacana that the community was involved in the communication planning process through (A) Adaptation, (G) Utilization of harvest results, (I) integrity, and (L) Maintenance of patterns for women farmer groups, but the government continues to strive to increase independence and welfare to improve family economy in utilizing empty land. This empowerment can increase income by meeting physical, spiritual, and social needs by utilizing community participation and resources available in 1000 Hydroponic holes of KWT Harmonis Ravacana, Tangerang City 2023.